Critical mission : essays on democracy promotion - Carothers, Thomas, 1956- (Washington, D.C. : Carnegie Endowment for International Peace, 2004)
Demand for practical knowledge and lessons about how the United States and other countries can more effectively promote democracy around the world has never been higher. This timely book by Thomas Carothers, one of the foremost authorities worldwide on democracy building, helps meet that need. Critical Mission draws together a wide-ranging set of Carothers's many seminal, widely cited essays, organized around four vital themes: the role of democracy promotion in U.S. foreign policy the core elements of democracy aid the state of democracy in the world the new U.S. push to promote democracy in the Middle East From puncturing myths about promoting civil society to sizing up the prospects for democracy in the Arab world, Carothers is consistently penetrating, incisive, and challenging to policymakers, democracy activists, and scholars alike. The book also includes the only up-to-date, comprehensive bibliography on democracy promotion.
Democracy and human rights : policy allies or rivals? (1994) -- Democracy promotion under Clinton (1995) -- The Clinton record on democracy promotion (2000) -- Ousting foreign strongmen : lessons from Serbia (2001) -- Promoting democracy and fighting terror (2003) -- Democracy promotion : explaining the Bush administration's position (2003) -- The core of U.S. foreign policy / Paula J. Dobriansky -- Carothers replies -- The rise of election monitoring : the observers observed (1997) -- Civil society : think again (1999) -- Western civil society aid to Eastern Europe and the Former Soviet Union (1999) -- The rule of law revival (1998) -- Promoting the rule of law abroad : the problem of knowledge (2003) -- Promoting democracy in postmodern world (1996) -- Democracy without illusions (1997) -- The end of the transition paradigm (2002) -- Debating the transition paradigm (2002) -- In partial defense of an evanescent "paradigm" / Guillermo O'Donnell -- The democratic path / Ghia Nodia -- Retaining the human dimension / Kenneth Wollack -- Tilting at straw men / Gerald Hyman -- A reply to my critics / Thomas Carothers -- Zakaria's complaint (2003) -- Democratic mirage in the Middle East (2002) / Marina Ottaway, Thomas Carothers, Daniel Brumberg, and Amy Hawthorne -- Is gradualism possible? Choosing a strategy for promoting democracy in the Middle East (2003) -- Democracy : terrorism's uncertain antidote (2003).
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Democracy; Democratization; Economic assistance; Democracy; Démocratie.; Démocratisation.; Aide économique.; assistance; democracy; POLITICAL SCIENCE -- General; Democracy; Democratization; Economic assistance; Democratie; Democratisering; Buitenlandse politiek; 89.35 democracy; Démocratie.; Démocratisation.; Politique étrangère.; Etats-Unis d'Amérique.; Monde; Außenpolitik; Demokratie; USA; United States of America; Foreign policy; International relations; Democracy; Development aid